2019
DOI: 10.3390/jcm8091333
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 18F-FDG PET/CT in Selecting Thyroid Nodules with Indeterminate Fine-Needle Aspiration Cytology for Surgery. A Systematic Review and a Meta-Analysis

Abstract: Thyroid nodules with indeterminate fine-needle aspiration cytology (FNA) represent a major challenge in clinical practice. We conducted a systematic review and meta-analysis evaluating the ability of hybrid imaging using fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) to appropriately select these nodules for surgery. PubMed, CENTRAL, Scopus, and Web of Science were searched until July 2019. Original articles reporting data on the performance of 18F-FDG PET/CT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Furthermore, low SUVmax values in PET/CT (a cutoff value ranging from 2 to 5) have a low reported risk for thyroid cancers [19,23]. In our study, only two patients with high SUV follicular neoplasm underwent thyroidectomy (false positive: 23%, 2/6) with benign pathologies, which is consistent with previous studies (0-39%) [8,23].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, low SUVmax values in PET/CT (a cutoff value ranging from 2 to 5) have a low reported risk for thyroid cancers [19,23]. In our study, only two patients with high SUV follicular neoplasm underwent thyroidectomy (false positive: 23%, 2/6) with benign pathologies, which is consistent with previous studies (0-39%) [8,23].…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have identified a high negative predictive value (83-96%) of 18 F-FDG PET/CT to rule out malignant thyroid nodules [22][23][24][25]. Superior diagnostic performance values of 18 F-FDG PET/CT are expected in patients presenting thyroid nodules with a diameter of >1 cm [19,22,24,25]. However, insufficient data exist to perform a subgroup analysis that excludes thyroid nodules with a diameter of <1 cm [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations